2020
DOI: 10.1177/1534484320905910
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Success Strategies for Employees With Autism Spectrum Disorder: A New Frontier for Human Resource Development

Abstract: The increased prevalence of young adults with Autism Spectrum Disorder (ASD) translates into a dire need to find ways to facilitate successful employment opportunities. Employment options are limited because of impaired communication and social skills that are vital for the workplace. There are a growing number of studies published on the need for employment, and primarily social psychologists, medical, and rehabilitation professionals have conducted this research; this necessitates multidisciplinary research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 99 publications
2
51
0
Order By: Relevance
“…These stressful experiences may also exacerbate co-occurring neuro-psychiatric conditions that are common among autistic individuals (Anderson et al 2020;Black et al 2020;Hedley et al 2018;Scott et al 2019). Other barriers are related to environmental factors such as stigma and a lack of modifications in recruitment processes and work environments (Black et al 2020;Johnson et al 2020;Nicholas et al 2018;Waisman-Nitzan et al 2020). This disadvantaged starting point makes this population especially vulnerable at times of global employment instability.…”
Section: Employment Implications Of Covid-19mentioning
confidence: 99%
“…These stressful experiences may also exacerbate co-occurring neuro-psychiatric conditions that are common among autistic individuals (Anderson et al 2020;Black et al 2020;Hedley et al 2018;Scott et al 2019). Other barriers are related to environmental factors such as stigma and a lack of modifications in recruitment processes and work environments (Black et al 2020;Johnson et al 2020;Nicholas et al 2018;Waisman-Nitzan et al 2020). This disadvantaged starting point makes this population especially vulnerable at times of global employment instability.…”
Section: Employment Implications Of Covid-19mentioning
confidence: 99%
“…In light of these challenges, we call to move away from employment perspectives that view diversity as 'the problem' and instead we suggest that the problem lies in inappropriate management of diversity (see also : Härtel and Fujimoto, 2015). Despite calls for more theoretical and empirical research on the inclusion of neurodivergent individuals into employment (Johnson et al, 2020), 90% of HR professionals in the UK reported that they do not consider neurodiversity in their people management practices (CIPD, 2018). Similarly, we know little about the well-being of neurodivergent employees beyond studies that show autistic minority groups suffer disproportionately from under and unemployment (Lever, 2016) as well as social isolation (Hedley et al, 2018) with potentially detrimental effects on their mental health (Mastroianni and Storberg-Walker, 2014).…”
Section: Human Capital and Neurodiversitymentioning
confidence: 99%
“…The subsequent sections introduce specific opportunities that could be adopted as potential solutions to the problematic areas identified. Johnson et al, 2020, Dreaver et al, 2020, Hayward et al, 2019 as well as technology-based interventions (e.g., Tomczak, 2020, Walsh et al, 2016 used to maintain, increase, and improve the functional capabilities of individuals with disabilities.…”
Section: Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations